Kelas Strategi Parenting dan Kesehatan Mental dalam Mengelola Keuangan Anak pada Wali Murid TK Kasih Bunda - Nur Hidayatul Istiqomah; M. Rizky Fauzi; Dwi Aminatus Sa’adah; Irfa’I Alfian Mubaidilla; Siswoyo Siswoyo; Filla Nor Faizah (Lembaga Pengembangan Kinerja Dosen, 2025)
This activity is a workshop that aims to provide insight and skills to the guardians of Kasih Bunda Kindergarten students regarding parenting strategies related to financial management and the importance of children's mental health. This activity discusses how to teach the value of money and financial management to children with educational and fun methods. The workshop was also accompanied by an interactive question and answer session, distribution of Supplementary Food (PMT) for children, and a group photo session as a symbol of togetherness. This activity has a positive impact in the form of increasing parents' knowledge about children's financial management, strengthening the relationship between guardians and schools, and supporting children's physical and mental growth and development.This study aims to determine the effect of price and product quality on purchase intention of Toyota Agya cars in Tuban City.